Zosteriform spiradenoma with spiradenocarcinoma: A rare entity - Satish A Adulkar; Atul M Dongre; Uday S Khopkar; Raghuram Maddala; Prachi V Gole; Siddhi Chikhalkar (Wolters Kluwer Medknow Publications, 2015)
Eccrine spiradenoma (ES) is an uncommon well-differentiated benign tumor originating from the sweat glands. It usually occurs as a single lesion in adults. Multiple ES in a linear or zosteriform distribution are rare. Spiradenomacarcinoma is an extremely rare tumor, which develops in an existing benign spiradenoma of several years of duration. We report a case of a 23-year-old- female patient with multiple spiradenomas arranged in zosteriform pattern and malignant transformation occurred in one of the lesions over a period of 10 years.